(untitled) (Al-Mansour Journal, 2022)
This research aims to identify the relationship and the impact of telecommunications regulators in promoting behaviors Morazán regulatory, accounting telecommunications regulatory one phenomena administrative crucial in helping the organization to carry out its functionsand duties, as increasing interest in strengthening behaviors Morazán regulatory substantial role in achieving the goals of both the organization and its employees in the same time, has indicated the research problem to the existence of a distinct lack of study after telecommunications regulators in promoting behaviors organizational citizenship of the sample surveyed, was chosen medium Bank for Boys as a field of application, have been adopted-resolution as a tool for research data that has been prepared based on the number of scales ready , and use statistical software ready (SPSS) in the introduction and analysis of research data and the most important statistical tools used in the analysis: "The percentage of repeat, and the arithmetic mean, and standard deviation and coefficient of variation, and the correlation coefficient for Spearman, and simple linear regression", has resulted in statistical tools for a number results confirmed mostly on the presence of correlation and the effect of any significant correlation between telecommunications regulatory and promoting behaviors citizenship organizational, these findings are consistent with the basic premise that launched them search, and it recommended a researcher on the need to increase the interest of the Organization surveyed studying how to activate the role of communications regulatory have and use in promoting behaviors organizational citizenship of its staff.